ADMINISTRATIVE PUBLIC SAFETY REGIMES IN THE EUROPEAN UNION - Bezzubov, Dmitry; Armash, Nadiia (Proceedings of National Aviation University (archive), 2017)
Purpose: to analyze existing threats, dangers and challenges the EU countries in terms of the present and the formulation of the basic foundations for the formation of the concept of ensuring public safety in the EU. Methods: Using a comparative method of scientific knowledge identified the major security threats in the EU and proposed substantive provisions of the administrative doctrine improve safety through the use of formal legal method. Results: the paper is dedicated to the problems of public security maintenance in the present-day context. Methods, techniques and strategies of public security maintenance as a scientific and public phenomenon are revealed. The levels of public security maintenance within the European Community are defined. Summarizing mentioned above, the concept of the service state in terms of the EU countries public security maintenance is the definition of course of development of the state mechanism and management of all administrative control branches. The main aim of which is to create mechanisms of risks and threats prevention with the respect to individuals’ rights, freedoms and legal interests in the societies of the EU countries. The concept of the service state as such is a practical result of the EU countries policy on elimination and neutralization of migration, military and terrorist threats. Discussion: in this article the author offers the basic provisions of the administrative doctrine enhance public safety in the European society.